The impact of temperature on wave interaction with damage in composite structures - Apalowo, R.K.; Chronopoulos, D.; Ichchou, M.; Essa, Y.; Martin De La Escalera, F. (SAGE Publications, 2017)
The increased use of composite materials in modern aerospace and automotive structures, and the broad range of launch vehicles’ operating temperature imply a great temperature range for which the structures has to be frequently and thoroughly inspected. A thermal mechanical analysis is used to experimentally measure the temperature-dependent mechanical properties of a composite layered panel in the range of −100 ℃ to 150 ℃. A hybrid wave finite element/finite element computational scheme is developed to calculate the temperature-dependent wave propagation and interaction properties of a system of two structural waveguides connected through a coupling joint. Calculations are made using the measured thermomechanical properties. Temperature-dependent wave propagation constants of each structural waveguide are obtained by the wave finite element approach and then coupled to the fully finite element described coupling joint, on which damage is modelled, in order to calculate the scattering magnitudes of the waves interaction with damage across the coupling joint. The significance of the panel’s glass transition range on the measured and calculated properties is emphasised. Numerical results are presented as illustration of the work.